Qualidade de sementes de Cupania vernalis (Cambess.) provenientes de remanescentes florestais da região Oeste do Paraná - Freitas, Laura Cristiane Nascimento de (2016)
The aim of the study was to characterize biometric and physical aspects and evaluate the physiological quality of seeds Cupania vernalis from different local harvest in three municipalities in western Paraná and standardize the tetrazolium test to assess the viability of seeds of C. vernalis. To evaluate the morphometry were measured the length, width and thickness of seeds and physical seed analysis was performed using the water content, mass of thousand seeds and dry matter. We evaluated the physiological quality by the germination percentage (% G), speed index (IVG) and mean germination time (TMG). Data were normal distribution analysis of waste and homogeneity of variances and later submitted to t test and Mann-Whitney test for nonparametric variables, the level of 5% error probability. To standardize the tetrazolium test, after soaking the seeds between paper for 48 h were tested five methods of preparation: intact seeds; cut at the opposite end to the heel end; partial removal of the integument; total removal of the integument; and total removal of the seed coat followed by slitting. The salt concentrations tested were 0,025%, 0,05%, 0,075%, 0,1% and 0,2% for times of 2, 4 and 6 h. When there was significant by F test, the results were subjected to analysis by response surface. In addition to seed the three places of harvest, a germination test was conducted using vermiculite as substrate chamber B.O. D at 25 ° C and an emergency test tubes of 120 cm3 volume, filled with commercial substrate with pine bark base and maintained in a protected environment with 50% shading. The averages obtained in the germination and emergence testing were compared with the tetrazolium test by the t-test and subsequently determined the Pearson coefficient. Among the local harvest, the seeds from the municipality of Nova Santa Rosa presented the lowest water content (39,5%). Seeds of the municipality of Rondon had higher mass of thousand seeds (235,98g), higher dry matter (0,120 mg-1) and larger morphometric dimensions, with average values of 9,66 mm, 6,08 mm and 8,05 mm for the length, width and thickness, respectively. There was no significant difference between % G and IVG, with average germination of 73% and 0,72 Twinning speed index. TMG was lower in seeds from the municipality of Nova Santa Rosa, taking 22 days to stabilize the germination. Morphometric, physical and physiological changes evidenced in this study can be attributed to the different climatic conditions prevailing in each harvesting site. The results obtained in the germination and emergence test, when compared with the tetrazolium test resulted in no significance, with a significant positive correlation of 0,96. Thus, it is recommended soaking for 48 h, complete removal of the seed coat and longitudinal seed, the concentration of 0,05% salt for 2 hours to evaluate C. vernalis seeds by tetrazolium